Interpretiranje plesnega izročila - Knific, Bojan (Traditiones (Ljubljana), 2013)
The variety among programmes of the European folk dance groups is partly linked to the diversity of dance and other traditions, but is due more to the selection of testimonies on dance tradition and their folklorization. Folk dance activity is namely actualized in emphasizing the distinctiveness of Our tradition from the tradition of Others. This is not only the case within national borders, where certain elements of the dance tradition of a certain area have been exposed and the others neglected, but even more so when we compare the perception and interpretation of traditions on an international level. Concerning the transformation of traditions into folk traditions, there exist transnational cultural areas with their own features that account for the resemblances among the programmes of the folk dance groups within the areas as well as the differences when comparing dances from different areas.
Keywords: ethnology; Etnologija; Ljudski plesi; Plesno izročilo; folklorizem; folklorne skupine